Fabrication and characterization of Eri silk fibers-based sponges for biomedical application - Silva, Simone Santos (2016)
Cocoon-derived semi-domesticated Eri silk fibers still lack exploitation for tissue engineering applications due to their poor solubility using conventional methods. The present work explores the ability to process cocoon fibers of non-mulberry Eri silk (Samia/Philosamia ricini) into sponges through a green approach using ionic liquid (IL) â 1-buthyl-imidazolium acetate as a solvent. The formation of Î²-sheet structures during Eri silk/IL gelation was acquired by exposing the Eri silk/IL gels to a saturated atmosphere composed of two different solvents: (i) isopropanol/ethanol (physical stabilization) and (ii) genipin, a natural crosslinker, dissolved in ethanol (chemical crosslinking). The sponges were then obtained by freeze-drying. This approach promotes the formation of both stable and ordered non-crosslinked Eri silk fibroin matrices. Moreover, genipin-crosslinked silk fibroin sponges presenting high height recovery capacity after compression, high swelling degree and suitable mechanical properties for tissue engineering applications were produced. The incorporation of a model drug â ibuprofen â and the corresponding release study from the loaded sponges demonstrated the potential of using these matrices as effective drug delivery systems. The assessment of the biological performance of ATDC5 chondrocyte-like cells in contact with the developed sponges showed the promotion of cell adhesion and proliferation, as well as extracellular matrix production within two weeks of culture. Spongesâ intrinsic properties and biological findings open up their potential use for biomedical applications.